Logic-based program synthesis and transformation : 25th International Symposium, LOPSTR 2015, Siena, Italy, July 13-15, 2015. Revised selected papers /: 25th International Symposium, LOPSTR 2015, Siena, Italy, July 13-15, 2015. Revised selected papers. (2015) - Unknown
No abstract available